(untitled) (Malaysian Management Journal, 1992)
The important relationship between the quality of human resource and the well-being of a nation has been repeatedly proven through examples from the past and present. Civilizations such as Greek and Islam and modern nations such as Japan, Korea and Switzerland flourish because of their human resources. Abundant natural resources necessarily do not guarantee the success of a nation, but abundant skilled human resources can creatively utilize limited natural resources. Thus, this paper seeks to explain the relationship between Human Resource Development (HRD) and becoming a developed industrialized society. The paper defines the concept HRD, explains factors that will influence HRD and outlines some approaches to HRD. In the final section, it looks specifically at HRD and industrialization process.